Elektra [videorecording (DVD)] - Bowman, Rob; Garner, Jennifer, 1972-; Visnjic, Goran, 1972-; Lee, Will Yun, 1975-; Tagawa, Cary-Hiroyuki; Stamp, Terence; Roe, Bill; Beck, Christophe (20th Century Fox Home Entertainment, 2005)
After recovering from seemingly mortal wounds, Elektra has been resurrected by her old mentor, Stick, who is then unable to keep her from working as an assassin for hire. Only when she balks at her latest assignment - killing Mark Miller and his young daughter, Abby - does Elektra finally come to grips with her damaged psyche. By not doing the job assigned to her, the assignment falls to the minions of "The Hand," an Asian sect dominated by supernatural forces under the control of the evil Roshi. Now Elektra will be in the ultimate battle between good and evil - a battle that will either take her life in a new direction or destroy her for good.